2015
DOI: 10.1136/bmjopen-2014-006966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroconvulsive therapy on cognitive functioning in patients with depression: protocol for a systematic review and meta-analysis

Abstract: IntroductionDepression is the leading cause of disability worldwide, affecting approximately 350 million people. Evidence indicates that only 60–70% of persons with major depressive disorder who tolerate antidepressants respond to first-line drug treatment; the remainder become treatment resistant. Electroconvulsive therapy (ECT) is considered an effective therapy in persons with treatment-resistant depression. The use of ECT is controversial due to concerns about temporary cognitive impairment in the acute po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 24 publications
0
9
0
4
Order By: Relevance
“…In addition to the small sample size of our study and lack of a validation design, weaknesses of our study include the absence of groups of patients with particular risks, such as schizophrenic or geriatric (>65 years of age) patients, who are allegedly at a high risk of experiencing memory and concentration deficits due to ECT. 18,19,[35][36][37] Furthermore, participants with known neurocognitive deficits were not examined. The resilient findings for the group of middle-aged patients examined in this study, which included no observed effects of ECT on speed of processing contrast with the results of other investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the small sample size of our study and lack of a validation design, weaknesses of our study include the absence of groups of patients with particular risks, such as schizophrenic or geriatric (>65 years of age) patients, who are allegedly at a high risk of experiencing memory and concentration deficits due to ECT. 18,19,[35][36][37] Furthermore, participants with known neurocognitive deficits were not examined. The resilient findings for the group of middle-aged patients examined in this study, which included no observed effects of ECT on speed of processing contrast with the results of other investigations.…”
Section: Discussionmentioning
confidence: 99%
“…It affects millions of people worldwide and is considered by the World Health Organization (WHO) to be one of the leading causes of disability 1 . Electroconvulsive therapy (ECT) is a well-established treatment for severe depressive episode 2 3 4 . Intravenous anesthetic medication before ECT is used to minimize subjective unpleasantness and adverse side effects of the induced tonic-clonic seizure.…”
mentioning
confidence: 99%
“…Future studies in this field should therefore use a larger battery of neurocognitive measures in order to obtain full insight in cognitive functioning across various domains. Currently, the effect of electroconvulsive treatment in depressed patients on multiple cognitive subdomains (memory-immediate recall, verbal memory-delayed recall, verbal memory-recognition, nonverbal memory-immediate recall, non-verbal memorydelayed recall, non-verbal memory-recognition, working memory, attention, intellectual ability, executive function, processing speed, spatial problem solving, global cognitive status, language, motor, and construction/visuospatial) is being studied (Oremus et al, 2015).…”
Section: Discussionmentioning
confidence: 99%